-
6y-7)(6y+7)=0
2.(x-3)[4(x-3)-x]=0
x-3)(4x-12-x)=0
3(x-3)(x-4)=0
x²+6x+17=0
6 -17*4*1<0, which cannot be decomposed, so it is unsolvable.
4.(2t+3)[(2t+3)-3]=0
2t(2t+3)=0
2y(y-3)=0
x+√2x-1+√2)x=0
x-8)(x+7)=0
0x-2)(1-x)=0
x-2)(x-1)=0
0x-1)(5x+4)=0
x-9)(x+8)=0
3x²+1=0
3x²>=0
3x²+1>0
No solution. 12.Think of x+1 as a whole.
x+1)-1][(x+1)-2]=0
x(x-1)=0
13.Take advantage of x -y = (x+y)(x-y)x-2) -2x+3) =0
x-2)+(2x+3)][x-2)-(2x+3)]=03x+1)(-x-5)=0
3x+1)(x+5)=0
14.(2x+3)²-4(2x+3)=0
2x+3)(2x+3-4)=0
2x+3)(2x-1)=0
x²-12+27=0
x-3)(x-9)=0
Everything that can be factored is decomposed, and the process is all here.
You don't have to write about the results.
-
(6y+5)(6y-5)-24=0
36y²+30y-30y-25-24=0
36y²-49=0
6y-7)(6y+7)=0
y=7 6 or y=-7 6
4(x-3)²-x(x-3)=0
x-3)(4x-12-x)=0
x-3)(3x-12)=0
x-3)(x-4)=0
x = 3 or x = 4
x+4)²-2x-1)=0
x²+8x+16-2x+1=0
x²+6x+17=0
6 -17 4 1<0, cannot be decomposed.
Therefore, there is no solution. (2t+3)²=3(2t+3)
2t+3)[(2t+3)-3]=0
2t(2t+3)=0
t=0 or t=-3 2
3-y)²+y²=9
2y²-6y+9-9=0
2y(y-3)=0
y=0 or y=3
1+√2)x²-(1-√2)x=0
x²+√2x²-x+√2x=0
x+√2x-1+√2)x=0
x=0 or x=1-2 2
x²=x+56
x²-x-56=0
x-8)(x+7)=0
x=8 or x=-7
x-2=x(x-2)
x-2-x(x-2)=0
x-2)(1-x)=0
x-2)(x-1)=0
x=2 or x=1
x(5x+4)=5x+4
x(5x+4)-5x+4=0
x-1)(5x+4)=0
x = 1 or x = -4 5
x-1)(x+2)=70
x²-x-2-70=0
x-9)(x+8)=0
x=9 or x=-8
x+1)²+2x(x-1)=0
x²+2x+1+2x²-2x=0
3x²+1=0
Because 3x >=0
So 3x +1>0
Therefore, there is no solution. (x+1)²-3(x+1)+2=0(x+1)-1][(x+1)-2]=0
x(x-1)=0
x=0 or x=1
x-2)²=(2x+3)²
x-2)²-2x+3)²=0
x-2)+(2x+3)][x-2)-(2x+3)]=03x+1)(-x-5)=0
3x+1)(x+5)=0
x=-1 3 or x=-5
2x+3)²=4(2x+3)
2x+3)²-4(2x+3)=0
2x+3)(2x+3-4)=0
2x+3)(2x-1)=0
x = 1 2 or x = -3 2
2(x-3)²=x²-9
2x²-12x+18-x²+9=0
x²-12+27=0
x-3)(x-9)=0
x=3 or x=9
-
3x+2)(2x-1)=0
Solution: 3x+2=0 or 2x-1=0
x1=-2/3,x2=1/2
2x-1) 2=3 (1-2x).
Solution: 4x 2-4x+1=3-6x
2x^2+x-1=0
x+1)(2x-1)=0
x1=-1, x2=1 Infiltration and Lack of Praise 2
-
1. The formula for square difference: (2x-1+x)(2x-1-x) = 0(3x-1)(x-1) = 0
3x-1 = 0 or x-1 = 0
The solution is x1 = 1 3, x2 = 1
2、(x-3)²-5-2x)² = 0
x-3)+(5-2x)][x-3)-(5-2x)] = 0(2-x)(3x-8) = 0
2-x= 0 or 3x-8 = 0
x1=2,x2=8/3
x+2)² = (x+2)(x-2)2(x+2)² x+2)(x-2) =0(x+2)[2(x+2)-(x-2)] = 0(x+2)(x+6) = 0
x1=-2, x2 = -6
4. Finished, x 11x + 30 = 0(x-5)(x-6) = 0
x1 = 5, x2 = 6.
-
1: (2x-1)^2-x^2=0
2x-1+x)(2x-1-x)=0 (3x-1)(x-1)=0 x1=1/3 x2=1
2. x^2-6x+9=(5-2x)^2
x-3)^2=(5-2x)^2 (x-3-5+2x)(x-3+5-2x)=0 (3x-8)(-x+2)=0 x1=8/3 x2=2
3. 2(x+2)^2=x^2-4
2(x+2)^2=(x+2)(x-2) 2(x+2)=x-2 x=-6
4. 10(x-3)+x=x^2
x^2-11x+30=0 (x-6)(x-5)=0 x1=5 x2=6
The third question upstairs was done incorrectly.
-
Please adopt the correct answer in time, and may help you next time, you adopt the correct answer, and you can also get wealth value, thank you.
-
1 x²-(2a+1)x+a²+a=0
Yes (x-a)(x-(a+1))=0
x = a or a+1
2 . 5x(3x-√2)-3√3 x+√6=015x-5 √2x-3√3 x+√6=0
3x-√2)(5x-√3 )=0
x= 2 3 or 3 5
3 .(1+√2)x²-(3+√2)x+√2=0.[(1+√2)x-√2](x-1)=0
x = 2 - 2 or 1
4 .x²-3|x|-4=0
x -3x-4 = 0 at 0
x+1)(x-4)=0
When there is x=4 x 0.
i.e. x +3x-4=0
x+4)(x-1)=0
x=-4, so x=4 or -4
-
(3x-1)^2-(x+2)^2=0
3x-1+x+2)(3x-1-x-2)=0(4x+1)(2x-3)=0
So: 4x+1=0 or 2x-3=0
Solution: x = -1/4 or x = 3/2
-
The squared difference formula breaks down, and then the equation is solved.
Unary quadratic equations.
There are four solutions, they are the direct leveling method and the matching method. >>>More
Divide by 3 to get x 2+2x-4 3=0
Recipe x 2+2x+1-1-4 3=0 x+1) 2-7 3=0 Then move the root to get two. >>>More
1 The concept of a quadratic equation includes three conditions: (1) an integral equation; (2) there is only one unknown in the equation; (3) The highest number of unknowns is 2". >>>More
First, the equation is transformed into the following form by shifting the term – n 2 is the 2nd power of n, and n (1 2) is the square root of n. >>>More
First, the equation is simplified, and the left side can be reduced to [5(t-4) 6] 2+[10(t-4) 9] 2=(25 36)*(t-4) 2+ >>>More